2012
DOI: 10.1007/s10597-012-9499-9
|View full text |Cite
|
Sign up to set email alerts
|

Help-Seeking for Emotional Problems in Major Depression

Abstract: To study help-seeking among the general population and people with major depression. 12-month help-seeking for emotional problems was assessed in a cross-sectional 2006 Estonian Health Survey. Non-institutionalized individuals aged 18-84 years (n = 6,105) were interviewed. A major depressive episode was assessed using the Mini-International Neuropsychiatric Interview. The factors associated with help-seeking, received help, and health service use were analyzed. The prevalence of 12-month help-seeking for emoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 35 publications
2
17
0
Order By: Relevance
“…Illness and symptom based need factors were assessed through structured interviews or questionnaires and were defined as professional judgements about people’s mental health status and therefore can be allocated to evaluated need, according to the “Behavioral Model of Health Services Use” [15]. Specifically, severity of depression was positively related to help-seeking in seven of the 16 datasets [31, 39, 40, 46, 47, 60, 61]. In addition, a longer duration of illness was positively related to help-seeking behaviour in six datasets [31, 34, 35, 40, 46] and was non-significantly related in three datasets [33, 38, 53].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Illness and symptom based need factors were assessed through structured interviews or questionnaires and were defined as professional judgements about people’s mental health status and therefore can be allocated to evaluated need, according to the “Behavioral Model of Health Services Use” [15]. Specifically, severity of depression was positively related to help-seeking in seven of the 16 datasets [31, 39, 40, 46, 47, 60, 61]. In addition, a longer duration of illness was positively related to help-seeking behaviour in six datasets [31, 34, 35, 40, 46] and was non-significantly related in three datasets [33, 38, 53].…”
Section: Resultsmentioning
confidence: 99%
“…However, in five datasets, this association was non-significant [34, 38, 40, 41, 60]. Demyttenaere, Bonnewyn [65] found that people with depression who had comorbid painful physical symptoms had lower rates of help seeking than those without these comorbid symptoms.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the symptoms of these illnesses are often overlooked, potentially leading to underappreciation, underdiagnosis, and undertreatment. 36,37 Secondly, although our study only included newly diagnosed cases to avoid potential effects of chronicity, it should be kept in mind that some of them may not be newly developed OSA cases. Patients might have had undetected OSA for years before being diagnosed.…”
Section: 30mentioning
confidence: 99%
“…Depressive symptoms can also predispose to metabolic syndrome (Vanhala, Jokelainen, Keinänen-Kiukaanniemi, Kumpusalo, & Koponen, 2009). Although effective treatments are available, only a minority of people suffering from depression seek and receive appropriate treatment (Hämäläinen, Isometsä, Sihvo, Pirkola, & Kiviruusu, 2008;Kim, Cho, Park, & Park, 2015;Kleinberg, Aluoja, & Vasar, 2013). There are many reasons for this, including lack of resources, lack of trained health care providers, social stigma associated with mental disorders and inaccurate assessment (World Health Organization, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Depression is also associated with increased health care utilization. According to Kleinberg et al (2013), depressed people use health care services from 1.5 to 3 times more often than the non-depressed. Depression has been shown to increase the risk of HCU among people with unhealthy BMI (Atlantis, Goldney, Eckert, Taylor, & Phillips, 2012) and among patients with diabetes (Chan, Lin, Chau, & Chang, 2012), cancer (Lo et al, 2013) and cardiovascular diseases (Chamberlain et al, 2011).…”
Section: Introductionmentioning
confidence: 99%